Accounting conservatism: Testing the effects of investment opportunity set and political cost - Blesia, Jhon Urasti; Setya, Gideon; Muslimin, Ulfah Rizky (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to examine the effect of investment opportunity set (IOS) and political cost (PC) on accounting conservatism in Indonesia. The population of this study is property and real estate companies listed on the IDX during the period 2011-2020. Using purposive sampling method which is based on certain considerations, it is obtained 20 companies with a total of 200 samples. This study uses Multiple Regression Analysis to examine the relationship between variables. The results of this study show that political cost has a significant effect on accounting conservatism. Meanwhile, the investment opportunity set has no effect on accounting conservatism. The results of this study are consistent with the political cost hypothesis as in the positive accounting theory that large companies tend to apply conservative accounting to reduce the amount of political costs they incur. The results of additional test on the enactment of PSAK 72 regarding income from contracts with customers in 2020 show that that there is no significant difference in accounting consevatism in property and real estate companies before and after the enactment of PSAK 72.